BGer 2P.159/2005 vom 30. Juni 2006 - Bundesgericht (2006)
Art. 5 Abs. 2 und 3, Art. 88 Abs. 1 und 2, Art. 9, Art. 26 Abs. 1, Art. 27, Art. 29 Abs 2, Art. 94 und 95 Abs 2 BV (Massnahmen gegen Dritte) | Grundrecht